2009
DOI: 10.1111/j.1651-2227.2009.01596.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous intrathecal baclofen therapy in children with cerebral palsy – when does improvement emerge?

Abstract: There seems to be a sequence of changes after introduction of continuous intrathecal baclofen in a child with cerebral palsy that may guide the multidisciplinary team in their timing of therapy during post-surgical follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…Baclofen inhibits afferent nerve fibers by binding to GABA B receptors in the dorsal horn of the spinal cord, and causes presynaptic inhibition of alpha motor neurons [3]. This restores proper function between the alpha motor neurons and muscle afferents, reducing abnormal muscle activity [4]. Baclofen in the cerebrospinal fluid may also affect periventricular areas in the brain if the baclofen concentration is high enough in the ventricles.…”
Section: Introductionmentioning
confidence: 98%
“…Baclofen inhibits afferent nerve fibers by binding to GABA B receptors in the dorsal horn of the spinal cord, and causes presynaptic inhibition of alpha motor neurons [3]. This restores proper function between the alpha motor neurons and muscle afferents, reducing abnormal muscle activity [4]. Baclofen in the cerebrospinal fluid may also affect periventricular areas in the brain if the baclofen concentration is high enough in the ventricles.…”
Section: Introductionmentioning
confidence: 98%
“…One retrospective study recommended directing the catheter tip to the cervical spine for better outcome in cases where spasticity involves all four limbs. The recommendations for the best practice surgical techniques for intrathecal baclofen therapy give specific positions for the intrathecal catheter tip, such as T10-12 for spastic diplegia, C5-T2 for spastic quadraplegia, and C1-4 for generalized dystonias [6,7]. However, a prospective study by Sivakumar et al [8] showed no correlation between the intrathecal catheter tip position and the baclofen maintenance dose in relation to the response to spasticity and outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Children and adults with dyskinetic CP spend most of their wake time sitting or sedentary, which makes the task of finding an optimal sitting position one of the most important goals for treatment in this group. According to Ramstad et al, 21 adjustments of sitting equipment in children with ITB need to be made after changes in dystonia and spasticity, depending on doses. 21 There was no change in ROM in the group after ITB.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ramstad et al, 21 adjustments of sitting equipment in children with ITB need to be made after changes in dystonia and spasticity, depending on doses. 21 There was no change in ROM in the group after ITB. However, no change can sometimes be positive, when deterioration is usually to be expected, which is often the case in CP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation